Usaha Pemanfaatan Tanaman Antagonis untuk Mengendalikan Meloidogyne incognita dan Meloidogyne graminicola - B. Triman; Mulyadi Mulyadi (Universitas Gadjah Mada, 2001)
The objective of the research was to find the antagonist plants for controlling the important plant parasitic nematodes i.e. Meloidogyne incognita on tomato and Meloidogyne graminicola on rice. The pots were arranged in Completely Randomized Design. Seven species of antagonist plants were used: Eclipta prostrata, Indigofera hirsuta, Digitaria sanguinalis, Eichhornia crassipes, Asparagus officinalis, Tagetes spp., and Crotalaria spp. Two experiments were done i.e. the antagonist plants were planted before the main crop and the antagonist plants were applied as an organic manure. The research results showed: 1) antagonist plants i.e.: Tagetes spp., I. hirsuta., Crotalaria spp., and A. officinalis inhibited the growth and development of M. incognita on tomato; 2) application of Crotalaria spp., E. prostrata., I. hirsuta, and E. crassipes as organic manure reduced the population development of M. incognita on tomato; 3) antagonist plants i.e.: E. crassipes, D. sanguinalis, Tagetes spp., Crotalaria spp. and A. officinalis inhibited the growth and development of M. graminicola on rice; and 4) the use of Crotalaria spp., Tagetes spp. D. sanguinalis, E. crassipes, A. officinalis and E. prostrata as organic manure reduced the population development of M. graminicola on rice.